2021
DOI: 10.21203/rs.3.rs-708099/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunomodulatory Activity, GC-MS Analysis and Pharmakokinetic Potential of Camellia Sinensis

Abstract: The immunomodulatory activities of medicinal plants are well-known. Medicinal plants found natural components enhance the immune system. However, both the Camellia sinensis is found a large number of bioactive compounds that make it strong to fight against ailments. It plays a significant role in cell-mediated and humoral immunity. The immunomodulatory activity of C. sinensis was carried out by neutrophil adhesion test, antibody titer and delayed-type hypersensitivity. The present study was aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Similarly, Moustafa et al [19] reported that dietary fenugreek seed powder improved the lysozyme activity in Nile tilapia. Tese results may be related to the immune-boosting functionality of fenugreek-derived biomolecules such as 4-aminoestradiol3-methyl ether [62], cyclohexasiloxane [63], decanoic acid [64], propenoic acid [65], and dicarboxylic acid [66].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Moustafa et al [19] reported that dietary fenugreek seed powder improved the lysozyme activity in Nile tilapia. Tese results may be related to the immune-boosting functionality of fenugreek-derived biomolecules such as 4-aminoestradiol3-methyl ether [62], cyclohexasiloxane [63], decanoic acid [64], propenoic acid [65], and dicarboxylic acid [66].…”
Section: Discussionmentioning
confidence: 99%